2015
DOI: 10.15430/jcp.2015.20.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibitors Against Topoisomerases and Histone Deacetylases

Abstract: Topoisomerases and histone deacetylases (HDACs) are considered as important therapeutic targets for a wide range of cancers, due to their association with the initiation, proliferation and survival of cancer cells. Topoisomerases are involved in the cleavage and religation processes of DNA, while HDACs regulate a dynamic epigenetic modification of the lysine amino acid on various proteins. Extensive studies have been undertaken to discover small molecule inhibitor of each protein and thereby, several drugs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Inhibitors of Top1 and Top2, currently developed, also exert their effect against other cancer-related targets [ 202 ]. Dual Top inhibitors, e.g., Top 1/2 [ 203 ], Top2/microtubule [ 204 ], or Top2/histone deacetylase [ 205 ], may exert improved efficacy. Besides, Top1 inhibitors are nonspecific RNA polymerase inhibitors.…”
Section: Future Strategies For Copper Complexes As Top Inhibitors mentioning
confidence: 99%
“…Inhibitors of Top1 and Top2, currently developed, also exert their effect against other cancer-related targets [ 202 ]. Dual Top inhibitors, e.g., Top 1/2 [ 203 ], Top2/microtubule [ 204 ], or Top2/histone deacetylase [ 205 ], may exert improved efficacy. Besides, Top1 inhibitors are nonspecific RNA polymerase inhibitors.…”
Section: Future Strategies For Copper Complexes As Top Inhibitors mentioning
confidence: 99%
“…The dual inhibitors are often characterized by high molecular weight that may reduce the chance of their drug abilities. Therefore, the safety profiles as well as pharmacokinetic properties need to be thoroughly considered in the design of dual inhibitors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of R-ICE and vorinostat for relapsed or refractory NHL patients also had 70% ORR (Budde et al, 2013). Pre-clinical experiments showed that SAHA and topoisomerase inhibitors surprisingly defeated lymphoma cells, and this might be a new aspect for NHL therapies (Seo, 2015).…”
Section: Application Of Hdacis In B Cell Lymphomamentioning
confidence: 95%